Social sustainability practices in Malaysian rural Libraries / Siti Khadijah Rafie … [et al.] - Rafie, Siti Khadijah; Abu, Roziya; Mohd Ali, Nor Amira; Mohd Nasir, Nur Syazana; Mohammad, Azlyantiny (UiTM Press, 2021)
The main purpose of this study was to investigate the practices of social sustainability in selected Malaysian rural libraries. A qualitative approach was employed through the observations, interviews and reviews of documents related to the selected six rural libraries involved in this study. This study concluded that all of the rural libraries involved in this study successfully implemented the social sustainability elements in their libraries.